ANALYSIS OF ACADEMIC SUPERVISION AND ORGANIZATIONAL CULTURE ON TEACHER PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENTING VARIABLEAT STATE MIDDLE SCHOOL 1 PINTU RIME GAYO, BENER MERIAH REGENCY - Sulman; Kiki Farida Ferine; Sri Rahayu (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This research investigates the influence of academic supervision and organizational culture on teacher performance, with job satisfaction as an intervening variable, at SMPN 1 Pintu Rime Gayo, Bener Meriah Regency. A quantitative approach was used with a saturated sample of 64 teachers (civil servants and PPPK). Data was collected through questionnaires, and analyzed using SmartPLS. The results reveal that academic supervision and organizational culture have a direct and significant positive effect on teacher performance and job satisfaction. Job satisfaction also has a direct and significant positive effect on teacher performance. However, job satisfaction does not mediate the relationship between academic supervision and teacher performance, but it does mediate the relationship between organizational culture and teacher performance. The study emphasizes the importance of academic supervision, organizational culture, and job satisfaction in enhancing teacher performance in the studied context.